The Yaz I–III Settlement Pattern in the Serakhs Oasis, Southern Turkmenistan. Issue 2 (3rd July 2017) - Buławka, Nazarij
ABSTRACT: The paper deals with the archaeological materials of the Yaz period from surveys carried out in the Serakhs oasis (Turkmenistan) by the Polish Archaeological Mission in 2007–2008 and the following seasons of archaeological work in the oasis, which brought to light 16 new sites of this period. The settlement analysis in the Serakhs oasis indicates that the changes that took place here are comparable to settlement dynamics in other regions of Central Asia during the Iron Age.